2015
DOI: 10.17795/zjrms-1042
|View full text |Cite
|
Sign up to set email alerts
|

CSF Protein Contents and Their Roles in Brain Development

Abstract: In early stages of development, the laminated structure of cerebral cortex is organized by proliferative, morphogenetic, and migratory processes. In these stages, cells within the ependymal lining of neural tube are thought to secrete embryonic cerebrospinal fluid (eCSF). As the neural tube closes, the choroid plexuses (CPs) secrete proteins such as growth factors, cytokines and morphogenes into the eCSF. The apical neuroepithelium is bathed with this fluid which plays regulatory roles in cortical cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In this paper hDPSCs cultured with the medium supplemented with E-CSF, we hypothesized that adding E-CSF to the culture medium could provide a suitable molecules for differentiation of hDPSCs into neuron similar to a microenvironment provided in embryonic period. Also, in this study, the results showed that our treated cells survive in sequential passages without losing their ability to proliferate which is probably related to HGF/c-Met signaling that caused to development and maintenance of the nervous system [17], also, the results of MTT assay showed that the neuron-like cells viability after induction by E-CSF was significantly higher than control group. In healthy brain, the neurotransmitters travel across the synapse but, neurodegenerative disease destroys the way electrical charges travel whithin cells [31].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In this paper hDPSCs cultured with the medium supplemented with E-CSF, we hypothesized that adding E-CSF to the culture medium could provide a suitable molecules for differentiation of hDPSCs into neuron similar to a microenvironment provided in embryonic period. Also, in this study, the results showed that our treated cells survive in sequential passages without losing their ability to proliferate which is probably related to HGF/c-Met signaling that caused to development and maintenance of the nervous system [17], also, the results of MTT assay showed that the neuron-like cells viability after induction by E-CSF was significantly higher than control group. In healthy brain, the neurotransmitters travel across the synapse but, neurodegenerative disease destroys the way electrical charges travel whithin cells [31].…”
Section: Discussionsupporting
confidence: 52%
“…In current study, the differentiated cells in the treated group connect with each other through synaptic -like connections, which may serve as the functional properties of the differentiated cells. One possible explanation for this event is component of E-CSF such as memberanous particle that have an effect on the modulation of signal transduction [17]. Hence a profitable line of future research might be to confirm this evidence such as physiological monitoring.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the fact that the protein fraction of the CSF is more complex in embryos than in adults, and that it is detected at higher concentrations [10], has led some authors to suggest that the E-CSF is involved in the regulation of neuroepithelial cell behavior. In addition, analysis of E-CSF shows that different mitogenic factors with various concentrations are present in this fluid including: nerve growth factor (NGF) [8], insulin like growth factors (IGFs) [24], vascular endothelial growth factor (VEGF) [25], and transforming growth factor-β1 (TGF-β1) [26]. In this study.…”
Section: Discussionmentioning
confidence: 75%
“…CSF contains cytokines, retinoic acid (RA), and diffusible factors such as transforming growth factor-ß (TGF-ß), nerve growth factor (NGF), brain derived neurotrophic factor (BDNF), insulin-like growth factor, and neurotrophin-3 which can regulate the survival, proliferation, and differentiation of neuroepithelium. Neurotrophins modulate various developmental processes such as neural differentiation in the adult and developing nervous system of vertebrates (Nabiuni et al, 2015). These factors have been shown to be involved in some brain functions such as connectivity of neurons and neurite outgrowth (Yoshi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%